2021
DOI: 10.1111/jir.12861
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of anticholinergic burden in adults with intellectual disabilities: a Scottish retrospective cohort study of n = 17 220

Abstract: Background Several drugs have anticholinergic side effects that are associated with adverse health outcomes. Anticholinergic burden studies in adults with intellectual disabilities (ID) have focused exclusively on older adults. This study investigates anticholinergic burden and its associations in adults with ID of all ages (17–94 years). Methods Adults with ID (n = 4 305), each with three general population age–sex–neighbourhood‐matched controls (n = 12 915), were linked to their prescribed medications with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Anticholinergic drug burden is associated with negative clinical outcomes including increased contact with services, hospitalisation, and dementia diagnosis [18]. A study of adults with ID and matched controls identified that people with ID have a higher anticholinergic burden and are more likely to be prescribed anticholinergic medication (OR 1.49, 95%CI: 1.38-1.59) [19]. Our study confirms this and further enumerates that those older with ID and epilepsy carry greater risk than their younger peers.…”
Section: Discussionmentioning
confidence: 99%
“…Anticholinergic drug burden is associated with negative clinical outcomes including increased contact with services, hospitalisation, and dementia diagnosis [18]. A study of adults with ID and matched controls identified that people with ID have a higher anticholinergic burden and are more likely to be prescribed anticholinergic medication (OR 1.49, 95%CI: 1.38-1.59) [19]. Our study confirms this and further enumerates that those older with ID and epilepsy carry greater risk than their younger peers.…”
Section: Discussionmentioning
confidence: 99%
“…Further details on sampling and linkage have previously been reported. 4 Anticholinergic medications were identi ed using the modi ed Anticholinergic Risk Scale (ARS) which was updated by the authors. 4 The ARS list classi es anticholinergic medicines as moderate (risk category 1), strong (risk category 2), and very strong (risk category 3), and is one of the more conservative anticholinergic burden scales.…”
Section: Study Cohortmentioning
confidence: 99%
“…4 Anticholinergic medications were identi ed using the modi ed Anticholinergic Risk Scale (ARS) which was updated by the authors. 4 The ARS list classi es anticholinergic medicines as moderate (risk category 1), strong (risk category 2), and very strong (risk category 3), and is one of the more conservative anticholinergic burden scales. There are numerous anticholinergic burden scales, although there is consensus of a cumulative total score of 3 or greater to be clinically at risk of adverse effects.…”
Section: Study Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…People with ID are particularly susceptible to polypharmacy due to the extensive medication regimens needed to manage these conditions [4]. Subsequently, people with ID have a high medication burden, especially from anticholinergics, sedatives and psychotropic medications, including antipsychotics [5][6][7][8][9][10][11]. While first-generation antipsychotics are known to cause a range of extrapyramidal symptoms, such as akathisia, tardive dyskinesia (TD) and dystonia, newer generation atypical antipsychotics produce cardiovascular and metabolic adverse effects [12].…”
Section: Introductionmentioning
confidence: 99%